Structure sensitive chemical reactivity by palladium concave nanocubes and nanoflowers synthesised by a seed mediated procedure in aqueous medium - Sreedhal, S.; Sudheeshkumar, V.; Vinod, C. P. (Nanoscale, 2014)
Palladium nanocubes and their transformation to concave nanocubes and nanoflowers are realised by a seed mediated procedure in aqueous medium and at room temperature using cationic surfactants. The concave nanocubes and nanoflowers were found to be enclosed by high index facets. The under coordinated atoms present on the high index facets make these nanostructures chemically more active towards Suzuki coupling and Heck coupling reactions compared to the conventional nanocubes and spherical nanoparticles of similar size.